The clinical cases of ketoacidosis in patients with 2 type diabetes treated with inhibitors of sodium-glucose co-transporter - Diana Sh. Avzaletdinova; Ilmira Z. Khabibulluna; Olga Y. Ibragimova; Tatiana V. Morugova (LLC "MEDIAFORMAT", 2021)
The diabetic ketoacidosis (DKA) is the most frequent urgent condition in patients with diabetes mellitus which requires hospitalization and results to mortality. The most common causes of DKA are the presence of concomitant diseases in diabetic patients, as well as the violation of the insulin therapy regimen. With the appearance of hypoglycemic drugs from the group of sodium-glucose co-transporter inhibitors (iSGLT2), isolated cases of DKA associated with their intake began to be recorded. This article describes 4 cases of ketoacidosis in patients with type 2 diabetes mellitus and type 1 diabetes mellitus taking dapagliflozin which is a hypoglycemic drug from the group of inhibitors of the sodium-glucose co-transporter.